How much can we rely on Broadsheet Journalism as the watchdog of Morality in the age of con artists? - Liu,Wei (2025)
Con artists, those who use their charm and confidence to scam people, are thriving in modern society. They signified the moral crisis in neoliberal culture, where morality, the idea of supporting group goods, is desensitized and secondary to individual profits. The media content played a crucial role in intensifying the crisis. The monetization of criminality indicates that moral transgression is costless and potentially valuable. Before this turns into social risks, for instance, a mimic of immoral behaviors as a career path. We expected that professional journalism could be a reliable moral watchdog to inform the public of this social threat. However, current studies on examining the watchdog role of journalists or framing analysis mainly focus on political or institutional events, leading to a vague understanding of how journalists construct modern complex and ambiguous con artists. To address the uncertainty, using the high-profile Anna Delvey as study case, this study employed a framing analysis of 96 newspapers, covering broadsheet and tabloid, left- and right-leaning outlets, with a moral dyad (TDM) perspective(agent-patient-causality) (Schein & Gray, 2018). Two framing strategies are identified: one framing focuses on Anna Delvey and her compelling story, which I termed as Inventing Anna Framing; another one discusses broad issues that Anna signified, such as the societal issues or regulations on media producers. Through examining the moral dyad patterns, this analysis argued that both framings ultimately constructed ambiguous moral dyad patterns despite narrative differences. According to TDM theory, these ambiguous moral narratives might weaken moral perception and judgment in Anna. Moreover, they might further result in the normalization of con artists and the tolerance of immoral behaviors, intensifying the desensitization of the morality crisis. Comparisons between broadsheet and tabloid, left- and right-leaning outlets are conducted and discussed, resonating with the broad discourses around objectivity, tabloidization, and moral clarity in journalism. While acknowledging that the broadsheets align with professional norms such as depth analysis, less emotionality, and impartial or carefully considered opinions, this study further argued that tabloid is also valuable in moral watching, refusing the pure critique of broadsheet has tabloidized. However, this study initially observed a “episode-ish” thematic framing pattern, which suggested a potential performance fulfilling watchdog roles. A stronger 3 moral condemnation of Anna and the legitimacy of monetizing criminality are found in right-leaning outlets, aligning with the conservative emphasis on traditional values and authority. These findings can contribute to journalism and morality studies, but also serve as a warning to contemporary journalists to pay attention to their own moral sensitivities and potential bias when reporting ambiguous social issues, especially on less political issues. Thus, this study finally suggests that moral clarity from journalists is not a betrayal of professional objectivity. It can be a clearer moral dyad portrayal of social events, and a straight message of immorality to inform the public of social threats. Considering the power of journalism in shaping public opinions, this clarity is important to be part of the watchdog role to increase the public’s moral sensitivity.
Keywords: Morality; Con artists; Journalism; Framing analysis; Theory of Dyadic Morality; Anna Delvey